HistoViewer: An interactive e‐learning platform facilitating group and peer group learning. Issue 3 (26th November 2012) - Sander, Bjoern; Golas, Mariola Monika
Abstract Understanding tissue architecture and the morphological characteristics of cells is a central prerequisite to comprehending the basis of physiological tissue function in healthy individuals and relating this to disease states. Traditionally, medical curricula include courses where students examine glass slides of cytological or tissue samples under a light microscope. However, it is challenging to implement group and peer group learning in these courses and to give students sufficient time to study specimens. An increasing number of medical schools have thus started to implement digital slide viewers, so‐called virtual microscopes, in histology and histopathology. These websites are mostly based on standard commercial software and offer limited adaptation to the special needs of first‐year students. An e‐learning platform has therefore been developed for use in cytology and histology courses. This virtual microscopy tool is coupled to a central database in which students can label and store the positions of individual structures for later repetition. As learning in pairs and peer groups has been shown to provide a high learning outcome, identified structures can be shared and discussed with students' peers or faculty via a built‐in communication module. This website has the possibility of opening an arbitrary number of frames which all can actively be moved and changed in magnification to enable the comparison of specimens and thus encourage a more global understanding of related tissues. HistoViewer is thus suggested as an e‐learning tool combining several modern teaching concepts. © 2013 American Association of Anatomists.